NOTA SÔBRE A ESPERMATOGÊNESE DE Nezara viridula (L.) (Hemiptera-Pentatomidae) - Piza Jor, S. de Toledo (REVISTA DE AGRICULTURA, 2016)
NOTA SÔBRE A ESPERMATOGÊNESE DE Nezara viridula (L.) (Hemiptera-Pentatomidae)